Primary Ewing sarcoma of the vertebral column: Case report and literature review - Lmejjati, Mohamed; Attar, Hicham El; Layadi, Fouad; Belaabidia, Badia; Ali, Said Ait Ben (Journal of Pediatric Neurology, 2007)
We describe a rare case of the spinal cord compression by a primary Ewing sarcoma of the thoracolumbar spine. A 16-year-old boy was admitted with back pain for 2 month and inability to walk for 15 days. At the presentation, he had paraparesis and bilateral hypoesthesia below the T12 level, without sphincter dysfunction. Thoracolumbar spine magnetic resonance imaging showed an involved vertebral body mass of the L1 extending in the epidural space with an extension into the prevertebral area. The mass was totally removed by the anterolateral approach. Histopathological examination revealed Ewing sarcoma. Although his infrequency, such a primary Ewing sarcoma of the vertebral column should be suspected for lesion causing a spinal cord compression particularly in the children and adolescent that the treatment protocol included a three main modalities: surgery, radiotherapy and chemotherapy.
Keywords: Vertebra; Ewing sarcoma; imaging; surgery